2023
DOI: 10.1007/s10648-023-09752-2
|View full text |Cite
|
Sign up to set email alerts
|

Does Professional Development Effectively Support the Implementation of Inclusive Education? A Meta-Analysis

Abstract: Inclusive education is a reform aimed at educating all students in general classrooms, independent of diversity features such as special educational needs, giftedness, or migration. Its successful implementation requires teachers with professional knowledge about inclusive education, skills to address the diverse needs in the classroom, and positive beliefs toward inclusive education. Teachers are provided with professional development opportunities, but are these effective in improving their learning process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 73 publications
2
8
0
2
Order By: Relevance
“…Professional development programs are frequently provided by educational institutions to enhance the lecturing skills of their educators. Nonetheless, few studies have investigated the effectiveness of various approaches to improving these skills (Donath et al, 2023;Mowbray & Perry, 2015). A study by Mowbray and Perry (2015) suggested that teacher professional development programs improved teachers' ability to design effective lectures.…”
Section: Teacher Professional Development and Quality Of Lecture Designmentioning
confidence: 99%
“…Professional development programs are frequently provided by educational institutions to enhance the lecturing skills of their educators. Nonetheless, few studies have investigated the effectiveness of various approaches to improving these skills (Donath et al, 2023;Mowbray & Perry, 2015). A study by Mowbray and Perry (2015) suggested that teacher professional development programs improved teachers' ability to design effective lectures.…”
Section: Teacher Professional Development and Quality Of Lecture Designmentioning
confidence: 99%
“…Policymakers must prioritize providing adequate funding and resources to schools, especially those in underserved communities, enhancing digital coverage. Implementing professional development programs for teachers to integrate technology effectively into their classrooms can ensure optimal use [59]. Collaborating with private-sector partners and using public-private partnerships can also facilitate the procurement of advanced technologies for mathematics instruction.…”
Section: A Policy Recommendations To Promote Equitable Access To Tech...mentioning
confidence: 99%
“…The study by Donath et al provides insight into how well professional development works to assist inservice teachers in implementing inclusive education [13] . To find out how professional development affected several inclusive education-related outcome variables, the study carried out a thorough meta-analysis.…”
Section: Teachers' Experience In Teaching Students With Senmentioning
confidence: 99%